DISTRIBUTION OF SIDEROPHILE ELEMENTS IN CR CHONDRITES: EVIDENCE FOR EVAPORATION AND RECONDENSATION DURING CHONDRULE FORMATION - A SURVEY - Kong P.; Ebihara M.; Palme H. (My University, 1999)
New data on the chemical composition of bulk samples, and of metallic and nonmagnetic fractions of six CR chondrites (Renazzo, Y793495, PCA91082, EET92042, Acfer 209 and El Djouf 001) are reported. It is shown that volatile siderophile element abundance patterns of metallic and nonmagnetic fractions of CR chondrites are complementary and volatility-dependent. In the metallic fraction CI-normalized abundances of Au, As, Sb and Ga decrease with increasing volatility, whereas in the nonmagnetic fraction abundances increase in the same sequence as in the metallic fraction. We argue that the siderophile element patterns of the metallic and nonmagnetic fractions reflect those of the chondrule and matrix fractions of CR chondrites, respectively, based on: (1) CR metal is mostly located inside chondrules and those metal grains outside chondrules probably were also derived from chondrules; (2) element partitioning within chondrules has been reset during chondrule formation; and (3) resetting of element distribution within chondrules occurred at sufficiently reducing conditions to allow partitioning of Au, As, Sb and Ga into CR metal.The complementary siderophile element patterns of CR chondrules and matrix are difficult to explain by gradual gas loss during condensation. The CI proportions of highly volatile elements in the bulk CR chondrites further argue against the possibility of loss of solids during condensation. Thus, the fractionation of volatile elements in CR chondrites is unlikely to be the result of gas-solid fractionation during condensation.The fractionation of volatile siderophile elements between CR chondrules and matrix requires evaporation of volatile elements during chondrule formation. The matrix pattern indicates recondensation of evaporated volatile elements. It appears, based on the composition of CR matrix, that the depletion and fractionation of moderately volatile elements in the bulk CR chondrites is due to formation of CR chondrites before complete recondensation of volatile elements which were evaporated during chondrule formation. This implies that agglomeration of CR chondrites proceeded simultaneously with chondrule formation.